Faktor-Faktor Yang Mempengaruhi Kinerja Bank Devisa Yang Terdaftar Di Bursa Efek Indonesia (2013-2017) - Hartanti Hartanti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2018)
Performance is a tool to evaluate the success of the company in running its business. This study aims to examine the performance factors of Foreign Exchange Banks Listed on the Indonesia Stock Exchange. Performance factors in this study were measured by the ratio of CAR, NPL, LDR, BOPO, GWM while Performance measured by ROA. This study uses quantitative analysis with multiple linear regression model to test the influence of these factors on the performance of foreign exchange banks simultaneously or partially. The results showed that there was a significant and simultaneous influence between CAR, NPL, LDR, BOPO, GWM on Foreign Exchange Bank ROA. Coefficient of determination simultaneously CAR, NPL, LDR, BOPO, GWM affect ROA of 85,6% and the rest influenced by other factors. Partially CAR, NPL and GWM have no significant effect on ROA of Foreign Exchange Bank. while the LDR and BOPO have a negative and significant effect on the ROA of Foreign Exchange Bank.